Patterns of hearing loss associated with bomb blasts (2013)
Bomb blast injuries are becoming an everyday scenario in Nigeria due to ever increasing act of terrorism. Such injuries in addition to affecting the functional living of the individual, is also accompanied with different patterns, nature, severity and types of hearing loss. The auditory mechanisms are usually affected as many victims of bomb blasts never get to use the hearing mechanism for adequate functional and communicative purposes. Against this background, a descriptive research design was conducted to investigate the patterns of hearing loss associated with bomb blasts. 45 victims of bomb blasts were assessed with the use of otoscopy, pure- tone audiometry (PTA) and tympanometry to ascertain their hearing thresholds and extent of hearing disability. The results showed that different patterns of abnormal audiogrammes and tympanogrammes of bomb blast ear injuries were evident among the participants, as there were more adverse effects of the explosion than could be imagined. Therefore, to every bomb blast, victims should consult audiologists for appropriate audiological rehabilitation and follow-up services; as hearing impairment from bomb explosions may have a lasting impact.